2018
DOI: 10.1021/acs.analchem.7b05304
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Chip with Integrated Electrophoretic Immunoassay for Investigating Cell–Cell Interactions

Abstract: Microfluidics have been used to create "body-on-chip" systems to mimic in vivo cellular interactions with a high level of control. Most such systems rely on optical observation of cells as a readout. In this work we integrated a cell-cell interaction chip with online microchip electrophoresis immunoassay to monitor the effects of the interaction on protein secretion dynamics. The system was used to investigate the effects of adipocytes on insulin secretion. Chips were loaded with 190 000 3T3-L1 adipocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 85 publications
0
35
0
Order By: Relevance
“…Furthermore, new processes to fabricate microfluidic channels from glass make this material attractive ( Wang et al, 2018 ). Islet on chip systems made from glass have been successfully fabricated and applied to investigate islet physiology and hormone secretion ( Dishinger et al, 2009 ; Lu et al, 2018 ). However, these systems were only partially made from glass and not ideally customized for parallel multi-parametric live-cell monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, new processes to fabricate microfluidic channels from glass make this material attractive ( Wang et al, 2018 ). Islet on chip systems made from glass have been successfully fabricated and applied to investigate islet physiology and hormone secretion ( Dishinger et al, 2009 ; Lu et al, 2018 ). However, these systems were only partially made from glass and not ideally customized for parallel multi-parametric live-cell monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, pancreas-on-chip systems made from glass described in the literature do not yet combine all these desirable features in a practical system for diabetes research. One reason for that is that these systems are only partially made from glass ( Lu et al, 2018 ; Shik Mun et al, 2019 ). Monolithic glass chips allow for rapid prototyping, show low unselective drug absorption, low autofluorescence and high transparency ( Piruska et al, 2005 ; Schwerter et al, 2016 ; van Meer et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Single islet and adipocytes were loaded in the chip, which resulted in an increase of insulin secretion by the adipocytes. They found that this was due to the release of non-esterified fatty acids, as assessed by electrophoretic immunoassay [ 109 ]. Natural killer (NK) cells act by using cell-to-cell interactions to kill target cells, an approach currently under investigation in cancer cell immunotherapy.…”
Section: Disease Diagnosticsmentioning
confidence: 99%
“…The microfluidic chip is a technology platform that integrates sample preparation, reaction, separation, detection, and other processes by controlling fluid flow in microchannels [1,2,3]. Since the first demonstration in 1990 [4,5], microfluidic chip electrophoresis (MCE) has developed rapidly with important applications in many areas, such as life sciences, biology, medicine, food, and environmental monitoring [6,7,8,9,10]. This method for protein analysis is automated, which allows for rapid separation, and high sensitivities and efficiencies [11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%